Politicization of Religion: Breaking the National Unity in Elections - Faridah, Siti; Mathias, Jerico (Law Research Review Quarterly, 2018)
The use of a dose of religion as a political instrument to gain power in elections is rife lately. Religion as something sacred is used as a powerful weapon to destroy society through differences in belief. Because religion is something sacred and personal in nature it makes it easy to politicize regarding this very sensitive issue. Religion as something that is sensitive makes everything that works with it becomes more emotional. This emotional involvement is built by belief in something supernatural. The politicization of religion has been made into a black politics that manipulates one's understanding and knowledge of religion by means of propaganda that intends to influence religion / belief in its efforts to bring interests into a political agenda. What is feared is that religion loses its noble values ​​when associated with politics or politicized (littered). The rejection of the politicization of religion is one form of efforts to glorify religion and prevent the destruction of the noble values ​​that exist in a religion and maintain the diversity and integrity of our nation.